Treatment of crude oil-contaminated sand: wetting, adhesion and cohesion: article - Salleh, Nurul Ashikin; Mat Shayuti, Muhammad Syafiq (2018)
Improvement of the sand treatment techniques requires detail information of the contaminated sand properties. Most of previous studies went detail on geotechnical properties of crude oil-contaminated sand or soil but not much on their other physical properties [4]. This research work characterized the physical properties of sand, crude oil and crude oil-contaminated sand namely density, viscosity, pH value, wetting, adhesion and cohesion study. The crude oilcontaminated sand and model sand sample were taken from Sabah field and Terengganu beach, Malaysia respectively while crude oil sample was from FPSO Cendor, Malaysia. Sand bulk and grain densities were measured using cylinder and analytical balance. For crude oil, its density and viscosity were measured using a graduated cylinder and automated viscometer AMVn respectively. pH value determination of crude oil was performed using Mettler Toledo pH meter . For wetting, adhesion and cohesion study, goniometer has been used for contact angle measure measurement. As a result, the bulk density of real and model sand sample were 1.3442 g/ml and 1.5342 g/ml respectively. The grain density of real sand sample using first and second method were 2.5713 g/ml and 1.4042 g/ml while for model sand were 2.1660 g/ml and 1.5306 g/ml respectively. The crude oil density obtained was 0.7845 g/ml while its kinetic, dynamic viscosities and pH value were 3.1071 mPa.s, 3.9607 mm2/s and 6.17 respectively. For wetting study, the contact angle between the crude oil and both sand sample surface were 0˚ which indicates the sand was strong oilwet.